Ekonomi Politik Masa Transisi: Kebijakan Afirmatif UMKM Menghadapi Ancaman Pasca-Ekstraktif (Post-Mining Era) di Tingkat Daerah - Suci Indah Sari; Ahmad Sholikin (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2024)
Regional economies heavily dependent on extractive industries often face the "resource curse," characterized by fiscal addiction and the marginalization of sustainable sectors. As mineral and oil reserves are finite, the transition to a post-extractive era becomes an existential necessity, positioning Micro, Small, and Medium Enterprises (MSMEs) as a critical "economic lifeboat." This study aims to analyze the political economy of Bojonegoro Regency’s transition strategy, specifically evaluating the alignment between political rhetoric and the actual implementation of affirmative policies for MSMEs amidst the region's massive oil and gas revenues. Using a qualitative approach with an embedded single-case study design, this research examines regional planning documents (RPJMD, Renja, and APBD) and incorporates in-depth interviews with key stakeholders, including local government planners, legislators, and MSME associations. The findings reveal an acute "fiscal narcosis" where the local government remains complacent due to high Revenue Sharing Funds (DBH) from the Cepu Block. Despite pro-MSME political rhetoric, fiscal commitment remains marginal, with MSME-related budgets accounting for less than 2% of the total APBD. Interventions are predominantly ceremonial and "business as usual," lacking structural transformation such as massive credit subsidies or market protection. This policy failure is driven by elite pragmatism and five-year electoral cycles, where leaders prioritize monumental infrastructure projects for instant political visibility and rent-seeking opportunities over long-term MSME development. The transition to a post-extractive era in Bojonegoro remains a "technocratic illusion." Without a radical shift toward a "Local Developmental State" model that prioritizes structural protection for MSMEs, the region faces a severe fiscal and social shock once extractive production ceases.